Trust and the choice between housing and financial assets: Evidence from Spanish households - Mayssun El-Attar; Markus Poschke (Institute for the Study of Labor (IZA), 2010)
Trusting behavior has been shown to affect households' portfolio choice between risky and risk-free financial assets. We extend the analysis of the effect of trust on portfolio choice to include the dominant component of households' portfolios, real estate. In a simple model, we show how the effect of trust on expected investment returns affects portfolio composition, including the share of real estate. Using data from the European Social Survey, we estimate individual-level trust as an unobserved attitude using survey questions on personal attitudes by applying a hierarchical item response model. Combining these estimates with data on Spanish households' financial decisions from the Survey of Household Finances (EFF) conducted by the Bank of Spain, we show that households with less trust invest more in housing and less in financial assets, in particular risky ones. Trust thus may drive not only (limited) stock market participation, but financial development more generally.
Keywords: D1; D8; Z1; 330; housing; trust; portfolio choice; item response models